Tephra fallout hazard assessment for a hydrovolcanic eruptive scenario in Mayotte - Audrey Michaud-Dubuy; Jean-Christophe Komorowski; Tristan Lacombe; Lucia Gurioli (Scientific Reports)
Abstract The new submarine volcano Fani Maoré offshore Mayotte (Comoros archipelago) discovered in 2019 has raised the awareness of a possible future eruption in Petite-Terre island, located on the same 60 km-long volcanic chain. In this context of a renewal of the volcanic activity, we present here the first volcanic hazard assessment in Mayotte, focusing on the potential reactivation of the Petite-Terre eruptive centers. Using the 2-D tephra dispersal model HAZMAP and the 1979 $$-$$ 2021 meteorological ERA-5 database, we first identify single eruptive scenarios of various impacts for the population of Mayotte. Even when considering the least impacting scenario, we show that ~ 30,000 people could be threatened by a future explosive eruption in the highly densely populated island of Petite-Terre. We then use a Monte Carlo approach to sample a series of eruptive scenarios and produce a probabilistic map allowing a long-term vision of the tephra fallout hazard in Mayotte. Finally, we discuss the probability of the different eruptive scenarios based on new field data and show that both Mamoudzou (Grande-Terre) and Petite-Terre could be impacted by at least 5 to 40 cm of tephra. These crucial results will be included in Mayotte’s first volcano emergency plan.